The sleep quality of patients with insomnia under the influence of subtle energy fields - Kryzhanovskii, Edvard V.; Yavorsky, Alexander B.; Kwong Choong, Lim (International Journal of Research in Medical Sciences, 2018)
Background: The article evaluates the current state of insomnia treatment for patients without neurological, psychiatric, and somatic disorders. An important goal consists in developing non-drug therapies for insomnia, possessing no side effects. Following this research direction, we put a special emphasis on non-medicamental methods for correction of sleep disturbance in persons with psychophysiological insomnia. Methods: Authors propose a method of insomnia treatment in which patients sleep on the specialized Bio Velocity mattresses (the ‘activated mattress’ therapy). The conditions of patients before and after the treatment are assessed by clinical, psychophysiological, electroencephalographic methods, and by the Voll method, which studies the meridians of organs and systems, including the nervous system. Results: We show the effectiveness of the therapy by demonstrating improving psychological indicators, EEG data, and the Voll diagnostics data in a group of patients. Conclusions: The activated Bio Velocity mattresses can effectively be used by patients with the sleep disorders in addition to and, partially, as a replacement of conventional tools and medicine.